(untitled) (TAMADDUN NURI JURNALI, 2024)
The Second World War had a significant impact on demographic processes in Uzbekistan and caused very complex changes in the political, economic and social spheres of life in the country. These changes, in turn, affected the demographic situation in the region. In this article, the author discusses this issue based on the opinion of scientists and analysis of archival data.